Alpha-defensin-dependent enhancement of enteric viral infection. - Sarah S Wilson; Beth A Bromme; Mayumi K Holly; Mayim E Wiens; Anshu P Gounder; Youngmee Sul; Jason G Smith (PLoS Pathogens)
The small intestinal epithelium produces numerous antimicrobial peptides and proteins, including abundant enteric α-defensins. Although they most commonly function as potent antivirals in cell culture, enteric α-defensins have also been shown to enhance some viral infections in vitro. Efforts to determine the physiologic relevance of enhanced infection have been limited by the absence of a suitable cell culture system. To address this issue, here we use primary stem cell-derived small intestinal enteroids to examine the impact of naturally secreted α-defensins on infection by the enteric mouse pathogen, mouse adenovirus 2 (MAdV-2). MAdV-2 infection was increased when enteroids were inoculated across an α-defensin gradient in a manner that mimics oral infection but not when α-defensin levels were absent or bypassed through other routes of inoculation. This increased infection was a result of receptor-independent binding of virus to the cell surface. The enteroid experiments accurately predicted increased MAdV-2 shedding in the feces of wild type mice compared to mice lacking functional α-defensins. Thus, our studies have shown that viral infection enhanced by enteric α-defensins may reflect the evolution of some viruses to utilize these host proteins to promote their own infection.